2022
DOI: 10.7759/cureus.23054
|View full text |Cite
|
Sign up to set email alerts
|

Spastic Paraparesis After SARS-CoV-2 Infection Without Radiological Changes

Abstract: Coronavirus disease 2019 (COVID-19) is primarily a disease of the respiratory system but severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may cause several immune-related complications including different neurological disorders, such as myelopathy with paraparesis. In this atypical case a female patient with progressive spastic paraparesis after COVID-19 infection, brisk reflexes and positive Babinski sign, reduced vibratory sensation to the thoracic level, elevated immunoglobulin levels (IgG) in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…On the other hand, 15 cases of MRI-negative myelitis/myelopathy associated with COVID-19, including the present cases, have previously been reported (Table 1) (7)(8)(9)(10)(11)(12)(13)(14)(15) The latency period from the onset of SARS-CoV-2 infection to the first neurological manifestations was three weeks or less in nine patients (mean: 12.7 days) and two months or more in five patients (mean: three months). Ten patients presented with neurological symptoms with subacute onset, and five patients presented with symptoms with acute onset.…”
Section: Discussionmentioning
confidence: 53%
“…On the other hand, 15 cases of MRI-negative myelitis/myelopathy associated with COVID-19, including the present cases, have previously been reported (Table 1) (7)(8)(9)(10)(11)(12)(13)(14)(15) The latency period from the onset of SARS-CoV-2 infection to the first neurological manifestations was three weeks or less in nine patients (mean: 12.7 days) and two months or more in five patients (mean: three months). Ten patients presented with neurological symptoms with subacute onset, and five patients presented with symptoms with acute onset.…”
Section: Discussionmentioning
confidence: 53%
“…Some patients may present delayed onset for 3 months after infection [7]. Some presented typical TM of paraplegia and sphincter dysfunction with normal spinal cord MRI [8][9][10], which caused diagnosis confusion and potential treatment delay [7]. These findings suggested that normal spinal cord MRI presentation may be a predictor of poor prognosis [6,9].…”
Section: Introductionmentioning
confidence: 99%